Making sense of freedom and responsibility - Nelkin, Dana Kay, 1966- (Oxford : Oxford University Press, 2011)
Dana Kay Nelkin presents a new account of freedom and moral responsibility, based on the view that one is responsible for an action if and only if one acts with the ability to recognize and act for good reasons. She responds to various challenges to the idea that we are free and responsible, and reaffirms our notion of ourselves as agents.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Free will and determinism; Responsibility